Lercanidipine's Antioxidative Effect Prevents Noise-Induced Hearing Loss - Zhaoqi Guo; E Tian; Sen Chen; Jun Wang; Jingyu Chen; Weijia Kong; Debbie C. Crans; Yisheng Lu; Sulin Zhang (MDPI AG, 2024)
Noise-induced hearing loss (NIHL) is a prevalent form of adult hearing impairment, characterized by oxidative damage to auditory sensory hair cells. Although certain dihydropyridines, the L-type calcium channel blockers, exhibit protective properties against such damage, the ability of third-generation dihydropryidines like lercanidipine to mitigate NIHL remains unclear.We utilized glucose oxidase (GO)-treated OC1 cell lines and cochlear explants to evaluate the protective influence of lercanidipine on hair cells. To further investigate its effectiveness, we exposed noise-stimulated mice in vivo and analyzed their hearing thresholds. Additionally, we assessed the antioxidative capabilities of lercanidipine by examining oxidation-related enzyme expression and levels of oxidative stress markers, including 3-nitrotyrosine (3NT) and 4-hydroxynonenal (4HNE). Our findings demonstrate that lercanidipine significantly reduces the adverse impacts of GO on both OC-1 cell viability (0.3 to 2.5 µM) and outer hair cell (OHC) survival in basal turn cochlear explants (7 µM). These results are associated with increased mRNA expression of antioxidant enzyme genes (HO-1, SOD1/2, and Txnrd1), along with decreased expression of oxidase genes (COX-2, iNOS). Crucially, lercanidipine administration prior to, and following, noise exposure effectively ameliorates NIHL, as evidenced by lowered hearing thresholds and preserved OHC populations in the basal turn, 14 days post-noise stimulation at 110 dB SPL. Moreover, our observations indicate that lercanidipine's antioxidative action persists even three days after simultaneous drug and noise treatments, based on 3-nitrotyrosine and 4-hydroxynonenal immunostaining in the basal turn. Based on these findings, we propose that lercanidipine has the capacity to alleviate NIHL and safeguard OHC survival in the basal turn, potentially via its antioxidative mechanism. These results suggest that lercanidipine holds promise as a clinically viable option for preventing NIHL in affected individuals.